3-DoF zero power micro vibration isolation via linear matrix inequalities based on H∞ and H2 control approaches. (15th May 2021) - Yalçın, Barış Can; Erkan, Kadir
Highlights: Each vibration isolation application requires different frequency standards. H ∞ and H 2 controllers have been intensively used in many fields of control theory. The realization of the quasi-infinite stiffness with zero-power property. The signal energy measurement method is used to measure the quasi-infinite stiffness. H ∞ and H 2 controllers are applicable for 3-DoF zero-power micro-vibration isolation. Abstract: Zero-power micro vibration isolators based on hybrid electromagnets, consisting of coils and permanent magnets, have potential usage in many industrial and academic fields, such as space laboratory operations in orbit, micro-nano assembly, clean room design, bio-engineering, stewart platforms, transportation, semiconductor manufacturing, suspension system design, and robotic surgery platforms etc . due to providing mechanical contact free micro vibration isolation with comparatively low energy consumption. Classical controllers optimized in time-domain do not show satisfying disturbance rejection performance for multi-directional mechanical disturbances varying at different frequencies. To tackle this problem, optimization techniques in frequency-domain are needed. In recent years, linear matrix inequality (LMI) based controllers have received lots of attention and become very popular due to their ability to satisfy multi-objective frequency-domain requirements. However, an experimental research including LMI based H ∞ and H 2 feedback controllers for a zero-power 3-DoF micro vibration isolator has not been conducted so far. In this study, H ∞ and H 2 controller types are employed to minimize the H ∞ and H 2 norms of both ground and direct disturbances for 3-DoF micro-scale vibration isolation with zero-power objective. Moreover, the experimental setup has been designed and manufactured to meet aforementioned goals. The design parameters of the experimental setup are explicitly given. The effectiveness of the proposed LMI structures for 3-DoF micro vibration isolation with zero-power problem is shown with the experimental results.